2007
DOI: 10.1111/j.1399-6576.2007.01470.x
|View full text |Cite
|
Sign up to set email alerts
|

Depth of anesthesia with desflurane does not influence the endocrine‐metabolic response to pelvic surgery

Abstract: The results show that there is no relationship between the intra-operative level of anesthesia depth achieved with desflurane and the extent of endocrine-metabolic stress response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
2
18
1
Order By: Relevance
“…So it can be concluded that hyperglycemia during inhalation anesthesia may be due to surgical pain and stimulation of sympathic system. The results of Baldini et al [17] study confirm this concept as this study showed that the depth of anesthesia with desflurane has no effect on the blood glucose during the surgery and even deep anesthesia with desflurane doesn't prevent hyperglycemia. In fact the reason of hyperglycemia during surgery may be surgical pain and metabolic response to surgical stress that even deep anesthesia cannot block these responses, but with enough analgesia we can maintain blood glucose in normal limits and prevent hyperglycemia and its complications during perioperative period.…”
Section: Discussionsupporting
confidence: 55%
“…So it can be concluded that hyperglycemia during inhalation anesthesia may be due to surgical pain and stimulation of sympathic system. The results of Baldini et al [17] study confirm this concept as this study showed that the depth of anesthesia with desflurane has no effect on the blood glucose during the surgery and even deep anesthesia with desflurane doesn't prevent hyperglycemia. In fact the reason of hyperglycemia during surgery may be surgical pain and metabolic response to surgical stress that even deep anesthesia cannot block these responses, but with enough analgesia we can maintain blood glucose in normal limits and prevent hyperglycemia and its complications during perioperative period.…”
Section: Discussionsupporting
confidence: 55%
“…A high or low isoflurane concentration has not been shown to have any effect on magnitude of blood pressure increase after stimuli in humans [47]. In another study on people, different concentrations of desflurane did not influence the endocrine response to surgery [52]. In the present study the end-tidal isoflurane concentration did not differ significantly between phases or the groups’ corresponding phases.…”
Section: Discussioncontrasting
confidence: 46%
“…Surgical wounding (breaching the skin) prompts a unique physiological response that is designed to maintain blood volume and institute body defences and wound healing. Cortisol secretion is an important part of this physiological response, 36 which occurs even in the complete absence of pain, such as when patients are unconscious and/or under full general anaesthesia 37–40 . A more protracted cortisol response following surgical castration does not necessarily indicate greater or more protracted pain compared with rubber ring castration.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol secretion is an important part of this physiological response, 36 which occurs even in the complete absence of pain, such as when patients are unconscious and/or under full general anaesthesia. [37][38][39][40] A more protracted cortisol response following surgical castration does not necessarily indicate greater or more protracted pain compared with rubber ring castration. It may simply indicate that there has been a greater breach of the skin.…”
Section: Discussionmentioning
confidence: 99%